Penatalaksanaan Fisioterapi Pada Kondisi Demensia Pada Usia Lanjut Stadium 1 Dengan Terapi Latihan Brain Gym Exercise dan Art Therapy - Intan Oktaviani; Putra Hadi; Adi Saputra Junaidi (3031-8572, 2022)
Dementia is a degenerative disease that often attacks people over the age of 60 years. Dementia occurs due to damage to brain cells where the nervous system can no longer carry information into the brain, resulting in a decline in memory, progressive skills, emotional disturbances, and behavioral changes, people with dementia often exhibit daily behavioral disturbances. lack of awareness and understanding of dementia results in prevalence and barriers to diagnosis and treatment when the elderly have dementia. The method used is a case study method with one respondent using the MMSE (Mini Mental State Examination) questionnaire. After doing physiotherapy with the intervention of brain gym therapy and Art Therapy for 6 exercises, the results of a fairly rapid increase in cognitive ability on the fifth day with an MMSE score of 20 but on the 6th day there was a decrease in the MMSE score to 19. Brain therapy gym and art therapy can improve cognitive abilities of patients with dementia stage 1